50 excellent extended essays (2008). - International Baccalaureat Organization ([S.l.] : IBO, 2008)
This CD-Rom includes essays in the following subjects: English a1, English B, Economics, Geography, history, Information technology in a global society, Philosophy, Psychology, Social and cultural anthropology, Biology, Chemistry, physics, Mathematics, Music, Visual arts, Politics, World religions.
Keywords: Extended essays; International Baccalaureate